Primitivní nonneurální nádor kůze z granulárních bunek (kazuistika) - Betlach, J; Kohout, A; Spacek, J (Ceskoslovenska patologie, 2006)
Primitive nonneural granular cell tumor was recognized in an 82-year-old man, mimicking a granuloma in the scalp. Despite its disturbing cytomorphology, this histogenetically enigmatic tumor with unusual immunoprophile (NK1-C3, CD 68 and NSE positivity; S-100 protein negativity) behaves indolently.
Keywords: Granular Cell Tumor; nádory kůže; Male; senioři nad 80 let; mužské pohlaví; Skin Neoplasms; Scalp; nádor z granulárních buněk; Aged, 80 and over; imunohistochemie; Humans; lidé; Immunohistochemistry; skalp